Respiratory Acid-Base Disorders: Respiratory Acidosis and Respiratory Alkalosis - Tinawi, Mohammad (Archives of Clinical and Biomedical Research, 2021)
Respiratory acid-base disorders are divided into respiratory acidosis (which can be acute or chronic), and respiratory alkalosis (which also can be acute or chronic). The diagnosis is made after obtaining arterial blood gases (ABGs). Respiratory acidosis is also known as primary hypercapnia and is due to an increase in carbon dioxide (CO2) tension in bodily fluids. The metabolic compensation is an increase in serum bicarbonate (HCO3−), the increase is more pronounced in chronic respiratory acidosis. Oxygen administration (O2) is critical in the management of respiratory acidosis. Respiratory alkalosis or primary hypocapnia is due to a decrease in CO2 tension in bodily fluids. The metabolic compensation is a decrease in HCO3−, the decrease is more pronounced in chronic respiratory alkalosis. Rapid correction of respiratory alkalosis should be avoided, and the underlying etiology should be addressed.